Analisis Klausa Adjektifal pada Buku "Rahasia Lancar Berkomunikasi" Karya Mulasih Tary & Devi Ardiyanti - Nur Azizah; Sabila Rahma Desfiyanti; Fanesa Eka Nurkhakimah; Nia Ramadhani; Nabila Agustin; Asep Purwo Yudi Utomo; Qurrota Ayu Neina; Oktarina Puspita Wardani (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This research examines adjective clauses in the book “Rahasia Lancar Berkomunikasi” by Mulasih Tary & Devy Ardiyanti. The study aims to analyze and reveal the formation, types of meanings, and functions of adjective clauses in the book, as well as their relation to real-life situations in society. The research uses a descriptive qualitative method with a theoretical approach, analyzing adjective clauses based on data by considering their structural formation and classifying them descriptively align with relevant theory. The adjective clauses found in the book “Rahasia Lancar Berkomunikasi” include those with meanings related to physical conditions, inner qualities, and emotional states. By understanding the formation, the type of meanings, and functions of adjective clauses in connection with everyday life, it is hoped that readers will gain better insight into effective language use. Knowledge of the role of adjective clauses in daily communication can serve as a foundation for society to interact more wisely and build good social relationships and it can assist in related fields.